Equilibrium Unemployment during Financial Crises - Andres Fernandez; Juan Herreno (Inter-American Development Bank (IDB), 2013)
Financial crises in both emerging and developed economies have been characterized by large output drops and spikes in unemployment and interest rates. To account for these stylized facts this paper builds a business cycle model where financial and labor market frictions interact as occasionally binding borrowing constraints and search frictions. The model is calibrated to a Sudden Stop-prone emerging economy and also to some peripheral European economies in the recent crisis. The model accounts for unemployment dynamics both during crises and at regular business cycle frequencies. The paper also assesses the welfare implications of policies that reduce real minimum wages during crises.
Keywords: E32; E44; F41; 330